Anaerobic fermentation of bird manure with cellulose waste - Golub, N.; Kozlovets, O. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2016)
The influence of component content cellulose raw material (wastes of paper, reed, hemp, and com) considered as a substrate for biogas and methane that the contents in it are compatible with the fermentation of the bird manure. It is shown that increasing the content of lignin and cellulose is hard for instant results and slows down the process of formation of biogas. The highest biogas yield is typical for using waste paper (cellulose) as substrate and is 371 cm3/g DOM by using the cane and hemp on 50% and 64% lower, respectively